An exploratory study on the usage of social media and its impact on the academic performance of UiTM Sarawak students at Campus 1 and 2 / Ketty Edden Edgar - Edgar, Ketty Edden (2017)
Social media is common things for those who are at the age of 18 to 24 years, as they are the generation that start to use social media (Yusop and Sumari, 2013). As we know, the use of social media is more on the teenagers as the media is more been exposed to them during this technology in this era. According to Yusop and Sumari,